2019
DOI: 10.1097/pra.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a 5-Week Inpatient Dialectical Behavior Therapy for Borderline Personality Disorder

Abstract: The goal of this study was to evaluate whether symptoms are reduced and emotion regulation improves when patients with borderline personality disorder (BPD) receive a 5-week course of inpatient dialectical behavioral therapy (DBT) and if changes in emotion regulation are associated with changes in symptoms. Methods: Forty-four patients with BPD receiving a 5-week course of DBT in a German psychiatry clinic participated. The short version of the "Borderline Symptom List" (BSL-23) was the patient-reported outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The utilization of DBT skills has also been associated with positive outcomes for individuals with bipolar disorder, primarily by increasing coping skills and decreasing associated emotion dysregulation (Eisner et al, 2017). Additionally, Probst et al (2019) 5-week inpatient adaptation of DBT is associated with decreases in BPD symptom severity and increases in emotion regulation (Probst et al, 2019).…”
mentioning
confidence: 99%
“…The utilization of DBT skills has also been associated with positive outcomes for individuals with bipolar disorder, primarily by increasing coping skills and decreasing associated emotion dysregulation (Eisner et al, 2017). Additionally, Probst et al (2019) 5-week inpatient adaptation of DBT is associated with decreases in BPD symptom severity and increases in emotion regulation (Probst et al, 2019).…”
mentioning
confidence: 99%
“…In comparison to the literature, the estimated effect sizes in the current studies were larger. Probst et al 35 found effect sizes between d = 0.38 and d = 0.47 for intention to treat analysis and completers using the BSL-23 while conducting a 5 week inpatient DBT treatment. Also, Probst et al 35 compared their effect sizes with effects reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 25% of patients seemed to refrain from self-harm within the first week of therapy 34 . Additionally, Probst et al 35 showed that a 5 weeks inpatient DBT therapy showed a significant reduction in BPD specific symptoms and improved emotion regulation. In addition, results indicate that symptom and functional improvement for shortened therapies were stable at 5 year follow-ups with annual measurements and readmission rates remained low after treatment completion 26,27 .…”
mentioning
confidence: 99%
“…General dysfunction is a key target in DBT therapy and predictor for individuals with personality disorders. Difficulties establishing and maintaining emotional regulation (e.g., negative affect, acceptance of emotions) (Probst et al, 2019 ) can be heightened if there is a co-occurring SUD (Grant et al, 2004 ). The preliminary findings of the current study indicate that while emotional dysfunction significantly decreased in both groups, the improvement was more modest among those with SUD.…”
Section: Discussionmentioning
confidence: 99%